Assessment of the ability of senior dental students of Esfahan University of Medical Sciences to detect interproximal caries on conventional bite-wing radiographs in 2012‒2013 educational year - Ehsan Hekmatian; Sayed Vahid Jalaie Esfandabadi (Isfahan University of Medical Sciences, 2013)
Introduction: Senior students of dentistry are known as those students who have finished all the theoretical and practical courses required to be able to detect carious lesions. Intraoral bite-wing radiographs are the most accurate radiographs for detecting interproximal carious lesions. The aim of the present study was to evaluate the ability of senior students of dentistry to detect carious lesions on conventional bite-wing radiographs.Materials and Methods: In this study descriptive/analytical study easy sampling technique was employed to select 551 interproximal surfaces on bite-wing radiographs. Two experienced dental practitioners detected carious lesions on the radiographs. Then the radiographs were assessed by 42 senior dentistry students (19 males and 23 females) and their reports were recorded. The results of assessments made by the students were evaluated by SPSS 11.5 using descriptive statistics, Cohen's kappa, paired t-test and ICC, and sensitivity and specificity values were determined (α = 0.05).Results: Kappa correlation coefficient for inter-student agreement and correct diagnoses was 0.22 (p value = 0.01); paired t-test correlation coefficient for the effect of gender on correct diagnosis was 0.31 (p value = 0.001); sensitivity was 0.234 and specificity was 0.969; false positive and false negative results were 3% and 76.5%, respectively. Mean percentages of correct diagnoses in the enamel and dentin were 22% and 23%, respectively.Conclusion: Under the limitations of the present study, it was concluded that the majority of teeth requiring restoration or other care measures based on radiographic evaluations are overlooked by senior dental students. On the other hand, the majority of sound teeth from a radiographic viewpoint are not erroneously diagnosed. Key words: Bitewing radiography, Dental caries, Students